Love the Lord your God with all your mind the role of reason in the life if the soul - Moreland, James Porter, 1948- (Colorado Springs, CO Navpress, 1997)
Includes bibliographical references.
Keywords: Faith and reason -- Christianity; Apologetics -- 20th century